Polypeptide Globular Adiponectin Ameliorates Hypoxia/Reoxygenation-Induced Cardiomyocyte Injury by Inhibiting Both Apoptosis and Necroptosis. (8th July 2021) - Zhu, Kaiyi; Guo, Jia; Yu, Xiaoxue; Wang, Que; Yan, Chao; Qiu, Quan; Tang, Weiqing; Huang, Xiuqing; Mu, Hongna; Dou, Lin; Bian, Yunfei; Han, Qinghua; et al.
Abstract : Adiponectin is a small peptide secreted and a key component of the endocrine system and immune system. Although globular adiponectin protects myocardial ischemia/reperfusion-induced cardiomyocyte injury, the protective mechanisms remain largely unresolved. Using a neonatal rat ventricular myocyte hypoxia/reoxygenation model, we investigated the role of its potential mechanisms of necroptosis in globular adiponectin-mediated protection in hypoxia/reoxygenation-induced cardiomyocyte injury as compared to apoptosis. We found that globular adiponectin treatment attenuated cardiomyocyte injury as indicated by increased cell viability and reduced lactate dehydrogenase release following hypoxia/reoxygenation. Immunofluorescence staining and Western blotting demonstrated that both necroptosis and apoptosis were triggered by hypoxia/reoxygenation and diminished by globular adiponectin. Necrostatin-1 (RIP1-specific inhibitor) and Z-VAD-FMK (pan-caspase inhibitor) only mimicked the inhibition of necroptosis and apoptosis, respectively, by globular adiponectin in hypoxia/reoxygenation-treated cardiomyocytes. Globular adiponectin attenuated reactive oxygen species production, oxidative damage, and p38MAPK and NF- κ B signaling, all important for necroptosis and apoptosis. Collectively, our study suggests that globular adiponectin inhibits hypoxia/reoxygenation-induced necroptosis and apoptosis in cardiomyocytes probably by reducing oxidative stress and interrupting p38MAPK signaling.